PENGARUH DISPLAY KELAS TEMATIK BERBASIS INTERAKTIF TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA DINI - Neni Komalasari; Dede Sulaeman; Ucu Siti Fatimah (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
This study aims to examine the effect of interactive thematic classroom displays on the ability of 45-year-old children to recognize number symbols 1-10 at PAUD El-Mahya Sukaluyu Cianjur. The problem stems from children's difficulty in recognizing number symbols, which is caused by passive teaching methods and a lack of interactive media. The research used a quantitative approach with a pre-experimental one group pretest-posttest design, involving 10 children from group A. Data were collected through observation, tests, and documentation. Data analysis included descriptive and inferential statistics (normality test, t-test, and simple linear regression). The results showed that the implementation of the interactive thematic classroom display was in the Very Good category (80.42%). There was a significant improvement in the children's ability to recognize number symbols 1-10, with the average pretest score increasing from 12.8 (Developing as Expected) to 16.4 (Developing Very Well) in the posttest. The interactive thematic display also had a significant positive effect on the children's ability to recognize number symbols. The coefficient of determination (R²) was 0.661, indicating that 66.1% of the variation in number symbol recognition ability can be explained by this variable.